Photovoice: Analysis Perception of Students' Experiences in Learning English Pronunciation Using the Elsa Speak Application - Nurul Alfi Soraya; Rafila Kasamira Dewi Abrori (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This research explored the perceptions of students at MAS Simbang Kulon Buaran Pekalongan about their experiences using the Elsa Speak application. Elsa Speak is an AI-based app that is easy to use and helps improve English pronunciation. Through photovoice research, positive impacts were observed and analyzed. The study found that using Elsa Speak helps students learn English pronunciation more effectively. This finding is supported by previous research on similar topics. The implication is that technology, like Elsa Speak, makes learning English pronunciation easier and more accessible for students.